Linux Administration - Cannon, Jason ([Place of publication not identifed] : Jason Cannon, 2016)
If you're looking to make the jump from being a Linux user to being a Linux administrator, this book is for you! If you're in windows administration and want to learn the ins and outs of Linux administration, start here. This book is also great for Unix administrators switching to Linux administration.
Introduction -- Booting -- System Logging -- Disk Management -- Managing Users and Groups -- Networking -- Linux Networking -- Network Troubleshooting -- Process Management -- File and Directory Permissions -- Managing Software -- Viewing and Editing Files -- Shell Scripting -- Conclusion -- About the Author -- Other Books by the Author -- Additional Resources -- Appendix: Trademarks.
Keywords: LINUX